Antibacterial activity of Cymbopogon citratus against clinically important bacteria - Geetha*, Subramaniam; Yew, Xin Ying; Lalita Ambigia*, Sivasamugham (Elsevier, 2020)
Antibiotic resistance has become a major problem worldwide, and has impacted patients emotionally and financially. In order to overcome this problem, alternative therapeutic agents should be investigated. Cymbopogon citratus possesses various pharmacological activities including antibacterial activity, which is useful in treating multidrug resistant bacterial infections. The antibacterial property is due to the presence of resistance modifying agents that are present in the plant. In this study, multidrug resistant bacterial isolates that have been collected from healthy individuals in Nilai were identified and confirmed. Aqueous and methanolic extracts of C. citratus were used in agar diffusion assays to determine the efficacy of C. citratus in treating multidrug resistant bacterial infections. Moreover, different parts of C. citratus were used to examine the difference in antibacterial activity. The inhibition zones were measured and compared among the different extracts and C. citratus essential oil, which was used as the positive control. The extracts were also compared with the antibiotics commonly used to treat multidrug resistant bacterial infections. In this experiment, C. citratus essential oil showed the greater antibacterial activity than methanolic extract due to the fact that the methanolic extract was not concentrated enough while boiled extract did not exhibit any antibacterial activity. The C. citratus extract also exhibited better antibacterial activity in gram positive bacteria than in gram negative bacteria, with the exception of P. aeruginosa which showed a high susceptibility towards the methanolic extracts. Thus, C. citratus could have the potential use in the treatment of biofilm development related infections.